Carbon supported hybrid catalysts for controlled product selectivity in the hydrosilylation of alkynes. Issue 5 (14th January 2021) - Roemer, Max; Gonçales, Vinicius R.; Keaveney, Sinead T.; Pernik, Indrek; Lian, Jiaxin; Downes, James; Gooding, J. Justin; Messerle, Barbara A.
Abstract : A series of Rh- and Ir-hybrid catalysts with varying tether lengths has been prepared by immobilization of Rh I, Rh III and Ir III complexes on carbon black, and applied in the hydrosilylation of alkynes. Abstract : A series of Rh- and Ir-hybrid catalysts with varying tether lengths has been prepared by immobilization of Rh I, Rh III and Ir III complexes on carbon black via radical grafting. The performance of the different catalysts was assessed for the hydrosilylation of phenylacetylene with Et3 SiH. The efficiency of the catalysts was dependent on the length of the tethers to the surface. The Rh III - and Ir III hybrids afforded the β( Z )-vinylsilanes, as observed for the analogous homogeneous Rh III catalyst. No distinct product selectivity was observed when using the homogeneous Rh I precursors as catalysts. However, on using the Rh III hybrid catalysts derived from the Rh I precursors to promote hydrosilylation, the major products were the α-vinylsilanes and the origin of the difference in reactivity was found to be a chemical modification of the catalysts during immobilization. Substrate scope is demonstrated for a number of alkynes, and feasible mechanisms supported by DFT calculations are proposed.